Impact of Climate Change on Oil Palm Productivity - Sri Gunawan; Betti Yuniasih; Miqdad Rachman Hidayat; Nurcahyono Nurcahyono (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
This study aims to analyze the influence of climate elements on oil palm productivity at the Pamukan Plantation in Kotabaru Regency, South Kalimantan. The observed climate elements include rainfall, air temperature, and air humidity. This study was conducted using an agronomic survey method and statistical analysis with regression and correlation, using secondary and primary data collected over the past six years (2015–2020). The results show that rainfall, temperature, and air humidity have a significant relationship with fluctuations in oil palm production. Increased rainfall beyond the optimal threshold actually reduces productivity, which is thought to be related to the hilly topography and the dominance of ultisol soils with low infiltration and water retention capacity. High water deficits, such as those experienced in 2015, negatively impact production the following year. Furthermore, increases in temperature and air humidity also show a negative relationship with production, due to disruptions in photosynthesis and plant transpiration. This study indicates that climate change could significantly affect oil palm productivity at the Pamukan Plantation. Therefore, adaptation strategies and plantation management are needed that are more responsive to changing climate conditions to maintain sustainable production.